Use of β-lactam/β-lactamase inhibitors for extended-spectrum-β-lactamase infections: defining the right patient population (2017)
β-Lactam/β-lactamase inhibitors (BLBLIs) were compared to carbapenems in two cohorts of hematological neutropenic patients with extended-spectrum-β-lactamase (ESBL) bloodstream infection (BSI): the empirical therapy cohort (174 patients) and the definitive therapy cohort (251 patients). The 30-day case fatality rates and other secondary outcomes were similar in the two therapy groups of the two cohorts and also in the propensity-matched cohorts. BLBLIs might be carbapenem-sparing alternatives for the treatment of BSI due to ESBLs in these patients.